The effects of ergonomic factors towards student’s satisfaction / Shazilla Salim, Nurul Ain Arif, Siti Zaidah Nadiah Rashid & Noor Khalida Hanim Harun - Salim, Shazilla; Arif, Nurul Ain; Rashid, Siti Zaidah Nadiah; Harun, Noor Khalida Hanim (2010)
Ergonomics is the science of designing user interaction with equipment and workplaces to fit the user. Ergonomic is important to prevent repetitive strain injuries, which can develop over time and can lead to long-term disability. It is also important to university because the best ergonomic factor provided will cause the students can study well due to produce excellence students in the future. Base on that, the aim of this study was to determine what ergonomics factors such as facilities, layout design and physical factor that are affecting student’s satisfaction in laboratories among FOMT student in UiTM Terengganu. The study based on a survey carried out from the questionnaires that are involving 223 respondents. By using the Pearson Correlation Coefficient testing, the relationships between every ergonomics factors that affect student’s satisfaction are examined. The finding shows that not all ergonomics factors are affected student’s satisfaction. This study showed, only layout design and physical factors are affecting student’s satisfaction but there is no relationship between facilities and student’s satisfaction. The findings of this study will help the university to improve their ergonomics factors provided to the students in achieving the student’s satisfaction due to produce the excellence students in the future. The further study are recommended because the researchers perceived that there is some others factors that will affecting student’s satisfaction such as mental factors.